Common injury incidences occur in Malaysian Taekwando athletes / Maisarah Mohd Saleh … [et al.] - Mohd Saleh, Maisarah; Abdul Hamid, Siti Fadhilah; Shahudin, Nurul Nadiah; Che Ismail, Che Muhamad Tarmizy (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2019)
This study was conducted to find out the injury incident among Taekwondo athletes during tournament and determined athlete’s performance after the injury. The method used was questionnaire given immediately after athletes finish their last game. Respondents were chosen randomly from three different tournaments with the total of 253 respondents. The result showed that most and least frequent injury was contusion and fracture. In addition, there was no significant different between gender towards pain scale level with male and female were not significant with, t (-0.74) = 3.38, p = 0.46(two-tailed). Moreover, there was no association between pain scale level and athlete performance after injury. The association showed that X (1) = 0.353, p = 0.341, means there was no statistical association between pain level and athlete performance. As a conclusion, Taekwondo was one of the combat sports that did not have much incident of severe injury and the change of rule did not give impact to the pattern of potential injury during tournament.